Sistema de Información y su incidencia en el control de datos de los deportistas de la federación de la provincia de Los Ríos cantón Babahoyo. - Moran Suarez, Zuly Jomira (2022)
The present investigation focused on finding the incidence factors in the data control of the information system of the athletes registered or to be registered in the federation of the province of Los Ríos canton Babahoyo. Which would hold as an objective to analyze the data collection processes of the athletes of the federation of the province of Los Ríos cantón Babahoyo, for the implementation of an information system. The investigation concluded the possible implementation of an information system and its impact on the data control of athletes, which was applied to the line of research Information and Communication Systems, Entrepreneurship and Innovation, related to the subline of athletes and Tecnogents of the logon Software and hardware.